Research of the Engagement Quality for AMT Clutch based on Varible Force Trajectory - Shan Waiping; Li Xiangsheng; Ye Wen (Jixie chuandong)
In the vehicle driveline system of the automatic mechanical transmission,the engagement quality of the clutch directly affects launching,shifting and the ride comfort,especially the launch quality of the vehicle. According to the basic rule of controlling the clutch in the process of launching and shifting,the control requirements for launching and shifting in automatic mechanical transmission through analysis the dynamics of the vehicle driveline system to determine three characteristics of the engaging force trajectory,following the trajectory characteristics defined six kinds of engaging force trajectories when engaging the clutch. In order to meet the requirements of clutch engagement quality when launching the vehicle,a new clutch force trajectory is determined through the comparative analysis of the influence of six kinds of engaging force trajectory on clutch engagement quality. And according to the evaluation index of the engaging quality of the clutch,a new force trajectory can be achieved by improving the structure of the clutch actuator and controlling the torque variation and the growth rate. The simulation results show that the determined new force trajectory can effectively improve the engaging quality of the clutch so as to achieve the purpose of improving the launching and shifting quality of the vehicle.